THE EFFECTIVENESS OF PHYSICS BASED RESEARCH IN LEARNING ENGINEERING PHYSICS - Usmeldi, U. (Jurnal Pendidikan IPA Indonesia, 2015)
This research aims to know the effect of implementation the research based learning to master properly physics concepts and students’ generic ability. This research used experiment method with pretest-posttest group control design. The results of this research were the research based learning was effective to improving students’ mastery of physics concepts and it was also developing the students’ generic ability. The recommendation suggested to lecturer of engineering physics is implementing the research based learning.